Diversidade funcional de aves aquáticas em áreas úmidas protegidas : tendências temporais e impactos da modificação de habitat. - Almeida, Bia de Arruda (2018)
We investigated temporal changes in waterbird communities within and between protected wetlands. We considered species richness and multiple components of the communities? functional structure and examined whether there are any discernable rules determining the assembly of communities at local and/or regional scales, and whether these rules change in time. We found that our waterbird communities are gaining species by filling ecological niches that were empty before. At the same time, differences in the trait space between wetlands are decreasing, showing that the gained species occupy similar niches in each wetland. This process may be possible due to an increase in the protection of the habitat and the availability of food resources. Thus, even though the environmental quality of the wetlands has not been fully restored, it seems that site protection is contributing to the recovery of functions performed by local communities of waterbirds. We also evaluated the functional structure and specific trait values of waterbird communities of natural, restored, and artificial wetlands in a same wetland complex. We found that wetland types do not form a simple gradient, so that there is not a decrease in indices from natural to artificial, with intermediate values for restored wetlands. Instead, the direction of difference varies according to the index and wetland type. In general, artificial wetlands support lower levels for most waterbird functional traits, as well as for functional dispersion, compared with natural and/or restored wetlands. We suggest that efforts to protect natural and restored wetlands are more effective to maintain the original diversity of waterbird functional traits than the compensatory construction of artificial ecosystems.